Impact of High Interest Rates on the Performance of Small & Medium Size Enterprises: A Case Study of Kabale Municipality. - Niwenyesiga, Anita (Kabale University, 2023)
The Small and Medium size enterprises present the most dynamic economic foundation for growth, income and employment creation. However, this vital sector has been greatly affected by the high interest rates being charged by financial institutions on borrowed capital in Uganda. The main objective of the study is to assess the impact of high interest rates on growth and financial performance of Small and Medium Enterprises in Kabale Municipality. The researcher will not only employ cross sectional research and descriptive but analytical research design also. Data will be collected basing on the objectives and questionnaires distributed to 50 respondents. Key words: Interest Rates, Performance, Small and Medium Enterprises